Progressive leukoencephalopathy caused by primary CNS lymphoma. Issue 4 (30th March 2010) - Matošević, Benjamin; Knoflach, Michael; Furtner, Martin; Gotwald, Thaddäus; Maier, Hans; Kiechl, Stefan; Willeit, Johann
Abstract : Prominent leukoaraiosis is common in the clinical routine setting. In addition to microatheroma and hypertensive small vessel disease (lipohyalinosis), a large number of rare but clinically relevant differential diagnoses have to be considered. A man in his 60s presented with left pontine infarction and subsequent rapidly deteriorating leukoaraiosis associated with dementia. Standard non-invasive examination did not enable the correct diagnosis to be obtained. A brain biopsy sample revealed a combination of diffuse infiltrating and intravascular large B cell central nervous system (CNS) lymphoma, which has not previously been described in literature. Despite immediate treatment with state of the art chemotherapy, the patient died 3 months after the onset of symptoms. Diffuse infiltrating and intravascular primary CNS lymphoma is a rare cause of rapidly progressive leukoencephalopathy and stroke mediated by neoplastic microvessel occlusion and inflammatory tissue damage. This report intends to increase awareness among neurologists and other stroke physicians about this disease in order to accelerate diagnosis and initiation of treatment.